Effects of supplementation frequency on nutritional performance and metabolism of cattle fed low-quality tropical forage - Silva, Tadeu E. da; de Oliveira, Cristhiane V.R.; Rodrigues, Aline N. [UNESP]; Palma, Málber N.N.; Camacho, Larissa F.; Rennó, Luciana N.; Franco, Marcia O.; Detmann, Edenio (Elsevier, 2024)
Our objective was to evaluate the nutritional performance and metabolism of cattle fed low-quality tropical grass forage and supplemented at different frequencies. Five rumen and abomasum fistulated Nellore heifers (386 kg body weight) were used in a 5 × 5 Latin square design. The five treatments were: control (without supplementation) and supplementation every 12, 24, 48, and 96 h. The amount of supplement provided was equivalent to 2.5 g/kg of body weight in a daily basis. Overall, supplementation had a positive effect (P<0.01) on voluntary forage intake. However, among the supplemented treatments, a decreasing linear effect (P<0.04) on forage intake was observed as the intervals between supplementations extended. The provision of supplements increased (P<0.02) body N accretion, rumen N balance, and microbial N production in the rumen. However, microbial N production responded quadratically (P<0.04) to the supplementation frequency, reflecting a sharp drop when supplement was provided every 96 h. An interaction between treatments and days of the supplementation cycle was observed for ruminal ammonia N (RAN; P<0.01). The interaction indicated day-to-day variations (P<0.01) when supplementation occurred every 48 or 96 hours. In these cases, RAN concentrations peaked (P<0.05) on supplement provision days. Urinary N excretion (UN) was higher (P<0.01) with the provision of supplements. However, UN showed an interaction effect between treatments and days of the supplementation cycle (P<0.01), where variations across days were only observed for supplementation every 96 hours. In this case, N excretion peaked (P<0.05) the day following supplementation. Infrequent supplementation strategies do not adversely affect the nutritional performance of cattle consuming low-quality tropical forages as long as supplementation intervals do not exceed two days.
Keywords: Forage intake; Nitrogen balance; Nitrogen metabolism; Ruminal ammonia